An investigation of druggable prognostic markers in paediatric ependymoma - Sabnis, Durgagauri (2016)
Background: Paediatric ependymomas are the second most common malignant brain tumours in children. Tumour recurrence, chemoresistance and invasion of surrounding critical structures are the hallmarks of ependymomas. These features are consistent with the cancer stem cell (CSC) hypothesis which states that tumours harbour a sub-population of stem-like cells which underlie therapeutic resistance. This study investigates the role of the radial glial stem cell marker BLBP, the multidrug transporter ABCB1, and the DNA repair enzyme MGMT in therapy failure in ependymomas with particular emphasis on the role of CSCs.